IN SEARCH OF THE MOON: The Hisab, Ru’yah, and Kashf - Musonnif, Ahmad (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2021)
This article deals with varieties of epistemological methods in calculating days of lunar calendar (hijri), mainly on the beginning date of months. Examining different methods in Indonesian Islamic-scape, it argues that there are three epistemological models which are rooted at Islamic classical epistemologies; the ahl al-hadith (textualist), the ahl al-ra‎y (contextualist), and the intuitive sufi. The ahl al-hadith emphasizes on the empirical rukyatul-hilal (witnessing the moon), whereas the ahl al-ra’y strongly concerns on the mathematically rational method. The sufi, not so popular in Indonesia but influential in some sufi circles, deploys the intuitive kashf (uncovering) method. In some cases, these three are however intertwined and in contradiction one to another. The article futher argues that different method-in-use is strongly influenced the local spesificties of diverse Indonesian Muslim’s backgrounds, and groupings.